Diamonds for quantum nano sensing. Issue 1 (February 2017) - Plakhotnik, Taras
Highlights: Great potential but significant progress is needed to become practical. Need for first principal verifiable modeling of dephasing processes in diamond. More research on the luminescence quantum yield and the ways to increase it. Call for high concentration of NV centers and crystals below 10 nm across. Search for new point defects with properties superior to NV centers. Abstract: This paper reviews applications of diamonds for sensing of magnetic and electrical fields, pressure and temperature. Considerable attention is focussed on the interaction of spins with static and oscillating magnetic fields as well as applications of such fields to spin control. A particular focus is on the spin of nitrogen-vacancy centers. Electron-spin microwave resonances play a central role in the ultra-sensitive metrology on the nanoscale, but pure optical methods are also considered in this review.